2012
DOI: 10.1039/c2an35964b
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Janus gold nanoclusters as excellent phase- and orientation-specific dopamine sensors

Abstract: This investigation, following our recent report on the one-pot hemi-micellar interfacial synthesis of Janus gold nanoclusters and the inter-cluster electron coupling establishing insulator-metal transition in the oriented Janus monolayers [Langmuir, 2010, 26(17), 14047], was to fabricate modified electrodes for sensing dopamine, the neurotransmitter. With a detection limit in the sub-nanomolar range, the apparent electron transfer rate constants for dopamine detection signified an intricate Janus cluster 2D ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 39 publications
(32 reference statements)
0
15
0
Order By: Relevance
“… 1 3 The collective properties of assembled Janus NPs have been proposed as potential solutions in different areas. Indeed, Janus NPs often carry multiple properties, which is of interest toward a variety of technologies such as catalysis, 4 emulsion stabilization, 5 sensing, 6 biomarking 7 and drug delivery. 8 When Au NPs are used as cores, Janus NPs can also display localized surface plasmon resonances (LSPR), thus providing the opportunity to tune collective optical effects arising from plasmon coupling in NP assemblies.…”
mentioning
confidence: 99%
“… 1 3 The collective properties of assembled Janus NPs have been proposed as potential solutions in different areas. Indeed, Janus NPs often carry multiple properties, which is of interest toward a variety of technologies such as catalysis, 4 emulsion stabilization, 5 sensing, 6 biomarking 7 and drug delivery. 8 When Au NPs are used as cores, Janus NPs can also display localized surface plasmon resonances (LSPR), thus providing the opportunity to tune collective optical effects arising from plasmon coupling in NP assemblies.…”
mentioning
confidence: 99%
“…The design and fabrication of electrochemical biosensors with improved analytical performance by exploring new concepts and sensor platforms where the interactions between biomaterials and nanoscale structures play key roles is a burgeoning area of research [22]. In this context, Biji et al [22] reported the use of Janus monolayer gold nanoclusters-modified with tetraoctylammonium ion (TOA + ) and tryptophan onto glassy carbon electrodes (GCE) to develop effective electrochemical sensors for dopamine (DA). A remarkable enhancement in the differential pulse voltammetric peak current value, a noticeable lowering in the LOD value (0.5 vs 6,400 nM), and better antifouling was found working with the Janus nanoparticle-modified electrode compared to the bare GCE.…”
Section: Janus Particles For Electrochemical (Bio)sensingmentioning
confidence: 99%
“…Schematic illustration of the Janus gold nanocluster modified GCE for the electrocatalytic oxidation of DA. Reprinted from[22] with permission.Although Janus nanoparticles offer the advantage for biosensing of two different faces with different chemical compositions allowing toposelective immobilization of complementary bioreceptors on these faces by using different specific ligands and different linking strategies[23], Pingarrón´s group was the first to explore the use of these nanoparticles for the development of electrochemical biosensors.Sánchez et al [24] used Janus Au-mesoporous silica nanoparticles (Au-MS JNP) as scaffolds to design an integrated electrochemical biorecognition-signaling system. They demonstrated the concept by covalent immobilization of HRP on the mesoporous silica face as enzymatic signaling element, and modification of the Au face with streptavidin (Stv) and polyethylenglycol (PEG) chains as biorecognition and solubilizing agents, respectively (Au-MS JNPHRP-Stv-PEG).…”
mentioning
confidence: 99%
“…Because CNT-based sensors have fast electron transfer kinetics, they offer low limits of detection of NTs. Carbon nanofiber electrodes and microelectrodes also offer high sensitivity for NT detection, and the limit of detection has been shown to be in nano-molar ranges [31,48,54,56,66,74]. Carbon nanofiber electrodes and microelectrodes have a small size with the ability to detect rapid changes of potentials, offering nanomolar ranges of NT detection.…”
Section: Applicabilitymentioning
confidence: 99%